Free radical scavenging activity of polyphenols - Mohd Adzim Khalili, Rohin; Che Abdullah, Abu Bakar; Alkasim Kabiru, Yunusa (2015)
Plants contain significant amount of polyphenols comprising of different groups such as flavonoids and phenolic acids which are further divided into subgroups. These polyphenols are known to prevent certain disease conditions by their ability to scavenge active free radicals species. Hence, the researchers today are emphasizing on evaluation of free radical scavenging activity of various plants parts and foods. A number of methods have been used to determine the effectiveness of the scavenging activity of a particular plant or food. The 1,1- diphenyl-2-picryl hydrazine (DPPH) is claimed to be the most widely used and efficient method for the measurement of scavenging activities of polyphenols due to it it’s simplicity and accuracy. Extraction of the bioactive and total phenolic compounds in plant is an important aspect in determination of the scavenging activity of plant part and food. In this present review, an attempt has been made to give an overview of extraction techniques of the bioactive compounds and various solvents used including their effectiveness and other wise, total phenolic and the free radical scavenging activities of various plant and foods sources.